PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA DAN KOMITMEN KERJA TERHADAP KINERJA PEGAWAI ( STUDI KASUS BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN JOMBANG ) - Sa’adah, Lailatus; Alamsyah, Achmad zarvendo (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2025)
The aim of this research is to determine the influence of organizational culture, work discipline and work commitment on the performance of employees of the Personnel and Human Resources Agency. The method used in this research is a quantitative method. The population in this study was 40 employees and the sample was 40 respondents using saturated sampling techniques. The data was collected using a questionnaire method, which was then analyzed using multiple regression analysis using SPSS version 26. The results of the research showed that there was a significant influence between Organizational Culture on employee performance, there was a significant influence between work discipline on employee performance, and there was an insignificant influence between work committees and employee performance. The results of the analysis of the coefficient of determination were 0.234, which means that 23.4% of employee performance variables were influenced by organizational culture, work discipline and work commitment variables, while the rest were influenced by other factors outside this regression model.